2008
DOI: 10.1176/appi.ps.59.11.1292
|View full text |Cite
|
Sign up to set email alerts
|

Use of Professional and Informal Support by African Americans and Caribbean Blacks With Mental Disorders

Abstract: Objectives-This study investigated the use of professional services and informal support among African Americans and Caribbean Blacks with a lifetime mood, anxiety, or substance disorder.Methods-Data were from the National Survey of American Life (NSAL). Multinomial logistic regression was utilized to test the use of professional services only, informal support only, both, or no help at all. Analyses controlled for sociodemographic characteristics, disorder-related variables, and family network variables.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 35 publications
9
51
1
Order By: Relevance
“…Two other recent studies using the NSAL look at the use of professional services and informal support specifically for a mental disorder (Woodward et al 2008;Woodward et al 2011). These studies found similar patterns of helpseeking to those described previously and few differences between African Americans and black Caribbeans; however, African American men were more likely than black Caribbean men to rely on informal support alone (Woodward et al 2011).…”
Section: Current Researchmentioning
confidence: 52%
See 2 more Smart Citations
“…Two other recent studies using the NSAL look at the use of professional services and informal support specifically for a mental disorder (Woodward et al 2008;Woodward et al 2011). These studies found similar patterns of helpseeking to those described previously and few differences between African Americans and black Caribbeans; however, African American men were more likely than black Caribbean men to rely on informal support alone (Woodward et al 2011).…”
Section: Current Researchmentioning
confidence: 52%
“…This research has suggested that similar to African Americans, black Caribbeans underutilize mental health services ). Further, observed racial differences in informal support networks for black Caribbeans and whites do not always mirror the differences found in comparisons of African Americans with whites Woodward et al 2008;Woodward et al 2010). More research is needed to thoroughly understand how demographic, socioeconomic, social network variables and racial discrimination differentially affect help-seeking actions across these groups.…”
Section: Heterogeneity Of Black Americansmentioning
confidence: 82%
See 1 more Smart Citation
“…A total CIS-R score of 12 or above is conventionally used to indicate the presence of common mental disorder (CMD) (to be referred to as 'cases' for subsample analyses). We further categorized individuals scoring above the threshold into having severe CMD (18+), mild/moderate CMD (12)(13)(14)(15)(16)(17) or being healthy (0-11) and used this measure as an independent variable.…”
Section: Clinical Variables Psychiatric Symptoms and Diagnosismentioning
confidence: 99%
“…There have been a large number of studies on informal help but they have focused on specific disadvantaged groups, such as gay men with HIV [10] or partner abuse [11] or demographic groups such as young people [12], and ethnic minority groups [13,14]. Seeking help from multiple sources has also been found [13].…”
Section: Introductionmentioning
confidence: 99%